(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article explores the historical, artistic, and scholarly significance of the epic heritage of the Kyrgyz people. It examines the origins of epics, their genre and thematic features, as well as the distinctions between heroic and social-domestic epics. Special attention is given to the work of Kayum Miftakov, his contribution to collecting and documenting oral folklore, and his collaboration with manaschi (epic storytellers). The study provides insights into epic works such as Manas, Kozhozhash, Er Tabylby, Kedeikan, Sarinzhi-Bokoy, among others, along with the life and creativity of Akbermet Karagul kyzy. The article emphasizes epic heritage as a spiritual treasure and a unique source reflecting the historical context and national identity of the Kyrgyz people.